2006
DOI: 10.3354/meps310129
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of imposex and seasonal patterns of gametogenesis in the invading veined rapa whelk Rapana venosa from Chesapeake Bay, USA

Abstract: The prevalence and intensity of imposex and observations on the seasonal gametogenic cycle are reported for the Asian veined rapa whelk Rapana venosa (Valenciennes, 1846), an invader of the Chesapeake Bay on the North American Atlantic coast. Adult whelks from opportunistic collections by commercial fishermen demonstrated inactivity from mid-November through early March, copulation from February through mid-November, and egg-laying activity from late May through August. All imposex females examined did not hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 21 publications
0
29
1
1
Order By: Relevance
“…Our present studies found wider spectrum of color gonads of both males and females, than is available in previously published material (Chuhchin, 1961a, 1984, Mann et al, 2006, Micu et al, 2009, Lanfrankoni et al, 2009, Saglam and Duzgunes, 2014. Moreover it is shown that the diversity of these colors is not (necessarily) associated with intersex status of individuals.…”
Section: Introductioncontrasting
confidence: 54%
See 4 more Smart Citations
“…Our present studies found wider spectrum of color gonads of both males and females, than is available in previously published material (Chuhchin, 1961a, 1984, Mann et al, 2006, Micu et al, 2009, Lanfrankoni et al, 2009, Saglam and Duzgunes, 2014. Moreover it is shown that the diversity of these colors is not (necessarily) associated with intersex status of individuals.…”
Section: Introductioncontrasting
confidence: 54%
“…In the western part of the Black Sea off the coast of Romania (Agigea littoral) the females (with no penis) had yellow gonads (Micu et al, 2009). Rapa whelk female gonads in Chesapeake Bay were completely yellow in color with special indication for "no penis" females (Mann et al, 2006). That qualification "no penis" is because of besides true females in Chesapeake Bay and in the Romanian Black Sea Agigea littoral area as well there were imposex females registered.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations